Effects of cutting size and organic acid on quality and enzyme activities of fresh-cut wax apple (Syzygium samarangense (Blume) merill & perry) - Kadir, Nur Izzah (2015)
Wax apple seems to be one of the potential fruits for fresh-cut market. The knowledge on fresh-cut wax apple is still lacking especially on their enzymes activity with respect to cell wall softening and tissue browning and how these enzymes could contribute in maintaining products’ quality. Thus, the study was conducted in order to gain more knowledge on the changes that occurred during the processing of fresh-cut wax apples that might be affected by cutting sizes and dipping treatment while remaining or maintaining the quality almost as good as intact fruits. In the first experiment, wax apples were stored as whole (control), halves, quartered,and wedged in domestic refrigerator (~50C) for nine (9) days and observed at 0, 3, 6,and 9 day. Water loss was observed to be increasing from day zero to day nine and also significantly related with the cutting sizes in which the whole wax apples lost the least amount of water compared to other cutting sizes. Firmness, total soluble solid, and ascorbic acid of wax apples were reduced significantly throughout the nine days of storage meanwhile the titratable acidity and pH value was observed to increase throughout the storage period. Since cutting sizes did not showed much significant differences on post-harvest qualities except for weight loss and titratable acidity, it is recommended to process wax apple into wedged (1/8) since they have the ability to retain their moisture by absorbing back more water from the condensation that could prevent weight loss. In conclusion, it is possible to use Syzygium samarangense as fresh-cut products as the changes in the qualities of fresh-cut wax apples was not critical in a way that they could reduce the market value of wax apples. For the second experiment, the wedged fresh-cut wax apples were dipped into three types of organic acids; ascorbic acid (AA), citric acid (CA), and oxalic acid (OA) at five different concentrations (0, 0.5, 1.0, 1.5 and 2.0%) and stored for nine days. The type of acids did not significantly affect water loss of the samples but the parameter was markedly varied under varying levels of acid concentration (P≤0.01) and storage period (P≤0.0001). The effect of acid concentration was apparently interacted significantly with period of storage (P≤0.01). The titratable acidity of fresh-cut wax apples was significantly affected by different type of acids but their effects on TA varied depending on their concentration. At a lower concentration of organic acids, the TA measured were similar to each other for AA, CA, and OA but the TA in the OAdipped fresh-cut wax apples started to increase significantly as the concentration of organic acids increased from 1.0 to 2.0%. In comparison to CA and OA, the concentration of AA dipping treatment caused the increased of the ascorbic acid content in fresh-cut wax apples without decreasing the pH that indicates sourness which can be an added value to fresh-cut wax apple in terms of nutrition. OA treated wax apples was recorded with the highest antioxidant activity which is 90.64% followed by CA (86.15%) and AA (81.17%) with the significant increased throughout nine days of storage period. Fresh-cut wax apples treated with OA (33.84 mg/100g) and CA (33.64 mg/100g) resulted in a significantly higher TPC in comparison to those dipped in AA (30.43 mg/100g) with the increased in TPC over nine days of storage period. As for enzyme activities, only pectin methylesterase and polyphenol oxidase activities were only affected by storage period whereas polygalacturonase activity was not affected by the treatment given. Overall, it can be concluded that the treatment with the 2.0% of ascorbic acid was proven to be beneficial for fresh-cut wax stored up to 9 days since it was recorded with the highest amount of ascorbic acid content or better known as vitamin C compared to other concentrations but at the same time, the pH remains similar to others that may suggest the retention of the flavours for the fresh-cut wax apples.